Association between exploratory activity and social individuality in genetically identical mice living in the same enriched environment. (19th November 2015) - Freund, J.; Brandmaier, A.M.; Lewejohann, L.; Kirste, I.; Kritzler, M.; Krüger, A.; Sachser, N.; Lindenberger, U.; Kempermann, G.
Highlights: The most active animals showed more social interaction, whereas least active mice showed more self-related behavior. Mice with greater roaming entropy (a proxy measure for global exploration behavior) were more individualistic. Roaming entropy also correlated negatively with latent factors representing non-social exploratory and play behavior. We hypothesize that more individualistic behavior would also be associated with more adult hippocampal neurogenesis. Abstract: We previously reported that inbred, genetically identical mice living in one enriched environment develop individual behavioral trajectories, indicating increasingly different levels of spatial exploratory behavior as quantified by roaming entropy. Cumulative roaming entropy (cRE) correlated positively with adult hippocampal neurogenesis, a type of plasticity involved in the flexible integration of new information into existing contexts (Freund et al., 2013). The study on which we report here was done in parallel to that first experiment, but here we acquired detailed observational data on the behavior of individual mice. Roaming entropy (RE) was again assessed in real-time with an antenna-based system over the entire experimental period of 3 months. Compared to the least active mice in the enclosure (low number of antenna contacts), the most active animals showed tendencies of increased socially interactive behavior in the final observation block whereas least active mice displayed more self-related behavior (non-social local exploration and play). When looking at roaming behavior, we discovered that RE correlated negatively with latent factors representing social exploratory and non-social exploratory and play behavior. Adult neurogenesis could not be studied in the present cohort but we do know that under identical conditions, cumulative RE correlated positively with adult hippocampal neurogenesis. We can thus hypothesize that the mice with more exploratory experience in terms of areal coverage (as quantified by RE) and related greater levels of adult hippocampal plasticity, might also be the ones that were less involved in interactions within the group and, hence, more individualistic. While this remains to be confirmed experimentally, the present data suggest that the described mechanism of individualization, which has previously been shown to be hippocampus-dependent, has a social component.